2022
DOI: 10.1093/oncolo/oyac009
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab Deruxtecan Improves Progression-Free Survival and Intracranial Response in Patients with HER2-Positive Metastatic Breast Cancer and Brain Metastases

Abstract: In the phase III DESTINY-Breast03 trial, trastuzumab deruxtecan improved progression-free survival (PFS) relative to trastuzumab emtansine across all patients with HER2-positive metastatic breast cancer, including a 75% improvement in PFS among those with baseline brain metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“… 40 , 41 , 42 In patients with stable BMs, both the DESTINY-Breast01 as well as the DESTINY-Breast03 demonstrated remarkable levels of intracranial ORR, with 58.3% (95% CI: 36.6%-77.9%) and 67.4%, respectively. 43 , 44 These data further confirmed T-DXd as a valid therapeutic option in this patient population with an unmet medical need.…”
Section: Antibody–drug Conjugates For the Treatment Of Her2-positive ...mentioning
confidence: 60%
“… 40 , 41 , 42 In patients with stable BMs, both the DESTINY-Breast01 as well as the DESTINY-Breast03 demonstrated remarkable levels of intracranial ORR, with 58.3% (95% CI: 36.6%-77.9%) and 67.4%, respectively. 43 , 44 These data further confirmed T-DXd as a valid therapeutic option in this patient population with an unmet medical need.…”
Section: Antibody–drug Conjugates For the Treatment Of Her2-positive ...mentioning
confidence: 60%
“…Evidence from the DESTINY-Breast03 study showed that the confirmed CNS ORR was 63.8% for T-DXd versus 33.3% for T-DM1. However, it should be pointed out that only patients with stable brain metastases were eligible in this trial and the type of local interventions as well as brain lesion radiotherapy status were not available [48]. A recent pooled analysis from the DESTINY-Breast01-02-03 trials of T-Dxd in patients with HER2-positive metastatic breast cancer having both treated and untreated brain metastases (BMs) at baseline (n = 148) reported an intracranial objective response rate (IC-ORR; i.e., CR and PR in brain lesions) in 45.2% and 45.5% of the patients with treated and untreated brain metastases, respectively.…”
Section: Trastuzumab Deruxtecanmentioning
confidence: 99%
“…The highly selective anti‐HER2 tyrosine kinase inhibitor tucatinib plus capecitabine and trastuzumab resulted in significantly better PFS and OS as compared with placebo plus capecitabine and trastuzumab in the overall population and in patients with brain metastases who were pretreated with trastuzumab, pertuzumab, and T‐DM1, as indicated by the HER2CLIMB study [ 213 ]. Pyrotinib and T‐DXd also showed impressive efficacy in HER2‐positive patients with brain metastases (Table 3 ) [ 209 , 214 , 215 , 216 , 217 , 218 , 219 ]. The development of novel anti‐HER2 drugs will expand the arsenal for treating HER2‐positive breast cancer patients, for whom continuous anti‐HER2 treatment is essential.…”
Section: Mbcmentioning
confidence: 99%